Konstruksi Identitas Sosial dan Budaya Konsumtif di Era Digital - Putri Astiti (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Advances in information technology have ushered society into the new media era, where social media is not just an information tool but also a new social space for teenagers. Instagram, as a visual-based platform, plays a significant role in shaping the reality of ideal lifestyles. Teenagers, who are in the process of discovering their identities, are susceptible to the influence of influencers and aesthetically constructed lifestyle trends on social media. This often triggers a shift in consumption patterns from functional to symbolic needs. This study used a qualitative descriptive approach. The subjects consisted of 10 students from the 2025 class of International Women University in Bandung, aged 18-20. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed through data reduction and presentation. The findings indicate that all subjects are active social media users, spending 4 to 9 hours per day. They use Instagram as a means of building their personal branding and seeking lifestyle references. There is a tendency for consumer behavior driven by four main factors: peer influence and the Fear of Missing Out (FoMO) phenomenon, the use of goods as symbols of social identity (sign value), exposure to persuasive content from opinion leaders or influencers, and consumption as psychological compensation (self-reward) to relieve academic stress. Students tend to make impulsive purchases of viral fashion, beauty, and culinary products to gain social recognition online.